Examining The Determinants of Halal Food Preferences in Gen Z: The Moderating Role of Motivation on Lifestyles and Purchasing Decisions - Prasasti, Riska; Ashwat, Natasya Ul; Gunawan, Syahrul; Azhar, Jeihan Ali (Likuid Jurnal Ekonomi Industri Halal, 2024)
This research aims to develop the Theory of Planned Behavior (TPB) by adding halal brands as an internal variable and investigating the influence of halal brands and technology as independent variables using the Theory of Planned Behavior (TPB) to make judgments about lifestyle and the purchase of halal food. The moderating effect of motivation on the link between attitudes, subjective norms, perceived behavioral control (PBC), lifestyle, and decisions to buy halal food is also investigated in this study. This research utilized a Gen Z sample, comprising 313 respondents. This study processes the data using the Smart PLS 3 program and a quantitative methodology with a Structural Equation Modeling (SEM) model. A Google Form was utilized to facilitate online data collecting, and it was shared through social media. The findings of the study indicate that opinions are significantly influenced by halal brands; Subjective norms are significantly impacted by technological variables; lifestyle and purchase decisions are significantly impacted by attitude variables; lifestyle and purchase decisions are significantly impacted by subjective norm variables; and lifestyle and purchase decisions are significantly impacted by the PBC variable. In the meanwhile, the interaction between attitudes, subjective norms, and PBC on lifestyle and purchasing decision is unabated by motivation.